2019
DOI: 10.1111/joa.13003
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic scaling patterns of lizard skin surface structure as revealed by gel‐based stereo‐profilometry

Abstract: The skin surface structure of squamate reptiles varies greatly among species, likely because it plays a key role in a range of tasks, such as camouflage, locomotion, self‐cleaning, mitigation of water loss and protection from physical damage. Although we have foundational knowledge about squamate skin morphology, we still know remarkably little about how intraspecific variation in skin surface structure translates to functional variation. This gap in our understanding can be in part traced back to: (i) our lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“…For example, Baeckens et al. (2019) showed that the skewness and kurtosis of the dorsal scales of Anolis cristatellus lizards scaled with body size; intriguingly, no such trend was observed for the ventral scales. Scientists of various disciplines are encouraged to use QuSTo to study functional variation in the skin surface topography of different species for both fundamental and applied research (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Baeckens et al. (2019) showed that the skewness and kurtosis of the dorsal scales of Anolis cristatellus lizards scaled with body size; intriguingly, no such trend was observed for the ventral scales. Scientists of various disciplines are encouraged to use QuSTo to study functional variation in the skin surface topography of different species for both fundamental and applied research (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Surface topography can be quantified by means of the surface roughness of a 2D profile taken along a cross‐section (e.g. Baeckens et al., 2019; Lauder et al., 2016; Wainwright et al., 2017, 2019). Among the different surface roughness parameters used in science and engineering, the arithmetic mean roughness or average roughness and root mean square roughness ( R q ) are commonly used to describe the degree of vertical relief in a 2D profile; in general, a greater surface roughness value indicates more prominent structures (Figure 3a).…”
Section: Qusto Program and Working Examplementioning
confidence: 99%
“…Liquid-preserved specimens are widely used for the study of skin surface ornamentation in squamates because the keratinized oberhautchen layer of the skin surface preserves well (Harvey, 1993;Irish et al, 1988;Martinez et al, 2021;Matveyeva and Ananjeva, 1995;Peterson, 1984;Riedel et al, 2015;Ruibal, 1968). Previous work has found no significant effect of preservation on anole skin surface structure (Baeckens et al, 2019). In order to eliminate any potential effect of ontogenetic or intersexual variation in skin surface anatomy and to increase statistical power, only male adult lizards were included in this study.…”
Section: Materials and Methods Specimensmentioning
confidence: 99%
“…Once the images are processed, a 3D-image of the surface is reconstructed to create a topographical representation of that surface. This surface profilometry approach has been validated in our previous research with known standards and used in the past to image other shark species, several bony fish species, cetacean skin, and other materials with known surface structure (Ankhelyi et al, 2018;Baeckens, Wainwright, Weaver, Irschick, & Losos, 2019;Wainwright et al, 2017Wainwright et al, , 2019.…”
Section: Gel-based Surface Profilometrymentioning
confidence: 99%